Missionary Men in the Early Modern World German Jesuits and Pacific Journeys - Strasser, Ulrike (Amsterdam University Press, 2020)
How did gender shape the expanding Jesuit enterprise in the early modern world? What did it take to become a missionary man? And how did missionary masculinity align itself with the European colonial project? This book highlights the central importance of male affective ties and masculine mimesis in the formation of the Jesuit missions, as well as the significance of patriarchal dynamics. Focussing on previously neglected German figures, Strasser shows how stories of exemplary male behavior circulated across national boundaries, directing the hearts and feet of men throughout Europe towards Jesuit missions in faraway lands. The sixteenth-century Iberian exemplars of Ignatius of Loyola and Francis Xavier, disseminated in print and visual media, inspired late seventeenth-century Jesuits from German-speaking lands to bring Catholicism and European gender norms to the Spanish-controlled Pacific. As Strasser demonstrates, the age of global missions hinged on the reproduction of missionary manhood in print and real life.